IMPLEMENTATION OF JEAN PEAGET’S THEORY OF CONTRUCTIVISM IN LEARNING: A LITERATURE REVIEW - Erawati, Ni Ketut; Adnyana, Putu Budi (Indonesian Journal of Educational Development (IJED), 2024)
The theory of constructivism, developed by Jean Piaget, emphasizes that knowledge is constructed through directexperience and social interaction. The implementation of constructivist principles in learning aims to create an environment that supports students' active exploration and deep understanding. This article examines various methods of applying Jean Piaget's theory in educational contexts, including problem-based learning, projects, hands-on experiments, and group discussions. The method used in this research is a literature review by reviewing several relevant literature studies related to constructivist learning. Where this learning was initially teacher-centered, constructivism has become student-centered to help them better understand abstract concepts. Although there are challenges in implementation such as teacher readiness and limited resources, the application of constructivism theory provides an opportunity to create a more meaningful and effective learning experience. The result of the literature review is that Jean Piaget's theory of constructivism in learning provides a strong framework for enhancing the learning experience, so by applying these principles, educators can create a more effective learning environment and holistically support students' cognitive development.